Effect of Zinc-enriched Bio-compost on Growth and Productivity of Transplanted Rice (Oryza sativa L.) - Miruna, M.; Immanuel, R. Rex; Baradhan, G.; Babu, S. (International Journal of Bio-resource and Stress Management, 2025)
The field experiments were conducted in two seasons during Navarai (Rabi, December, 2023–March, 2024) and Kuruvai (Kharif, June–October, 2024) at the Experimental Farm of Department of Agronomy, Annamalai University, Annamalai Nagar, Chidambaram, Tamil Nadu, India to assess the effectiveness of Zinc-Enriched Bio-compost in enhancing the growth, yield and economics of transplanted rice. The experiments were laid out in a randomized block design with eight treatments and three replications. In the present study, compost made from crop residues and cow dung (maize-stover+Albizia saman leaf litter+cowdung at 3:1:1 ratio) was enriched with ZnSO4 (0.0, 1.0, 1.5, 2.0, 2.5 and 3.0% on w/w basis) along with bio-fertilizers (Azospirillum, Pseudomonas, Phosphobacteria and ZSB each at 0.2%) were used. The application of zinc enriched bio-compost significantly affected the plant growth parameters, physiological attributes and yield parameters. This also led to higher grain and straw yield as well as better economic returns compared to the control. From the study, it was observed that the best combination of zinc enriched bio-compost for optimum growth, yield and economic performance of transplanted rice was 0.5 t ha-1 of crop residue compost enriched with 2.0% ZnSO4 (10 kg (0.5 t ha-1)-1 of bio-compost) along with biofertilizers. The study concluded that zinc-enriched bio-compost application could be recommended as a sustainable and economically viable strategy for improving the growth, productivity and profitability of transplanted rice.